KEPADATAN POPULASI CAPUNG Crocothemis servilia (Odonata: Libellulidae) PADA PERTANAMAN PADI SAWAH DI KELURAHAN ANDURING KECAMATAN KURANJI PADANG SUMATERA BARAT - Gustia, Nuri; Jasmi, Jasmi; Pratiwi, Putri (Pendidikan Biologi, 2014)
ABSTRACT Dragonflies (Odonata:  Libellulidae)  have  an  important  role  in  rice  field  ecosystem. Dragonflies can serve as an indicator to monitor the water quality of surrounding environment and predators on crop pests of rice, in addition to the dragonfly also play a  role in  health and agriculture. Crocothemis servilia is commonly found in rice crops. So far there are no data on the density of dragonflies (Odonata) including dragonfly C. servilia in the District of Kuranji Anduring. The purpose of this study was to determine the population density of  C. servilia dragonflies (Odonata: Libellulidae) on Rice Planting in Anduring Kuranji District of Padang in West Sumatra. This study was conducted in January-February 2014, with a descriptive survey method. It is by way of direct collection of the C. servilia existing research in the location. Field sampling done at night on dry rice and wet rice fields when the bright moon and new moon. Physical environmental factors measured are temperature and humidity. The area used as a place of research about + 1 Ha. The characteristics of C. servilia which are found are the average length of the male dragonfly C. servilia abdomen is 30 mm long and 27 mm in females. Body of male colored blood red and the female body colered yellow, have teeth, rear wing wider than the front wing, transparent wings with wing base yellowish, eyes slightly purplish red bull and there is a black line along the abdomen . While the female abdomen is yellowish brown with a bla ck stripe along its abdomen, have compound eyes and a pair of antennae are short and fine size. The average of  population density of C. servilia in the rice fields location of Anduring Kuranji District of Padang in West Sumatra on dry fields individu/m2 is 0.15, and the wet rice fields (aqueous) was0.09 individu/m2 .